Application of sewage sludge derived hydrochar as an adsorbent for removal of methylene blue - Diwakar Kumar Singh; Anurag Garg (Sustainable Chemistry for the Environment, 2024)
Hydrothermal pretreatment (HTP) is used to convert biomass into hydrochar (HC) through the application of heat and pressure in a water-based medium. The HC has emerged as a promising material for various environmental applications including wastewater treatment, soil amendment, and carbon sequestration. In this study, the applicability of sewage sludge (SS) derived HC was tested as an adsorbent for methylene blue (MB) dye removal from wastewater. The HC was also subjected to chemical activation with KOH before the adsorption study. The HC samples were characterized for structural morphology and molecular functionalities using instrumental analysis. All the HC samples exhibited almost similar adsorption capacity (∼190 mg/g) for MB after 24 h of contact time (MB concentration = 200 mg/L, solution pH = 7 and adsorbent dose = 1 g/L). The equilibrium data could be adequately fit in Langmuir model equation. The negative value of free energy indicated favorable MB adsorption process. The study demonstrated that the SS derived HC can be recycled as adsorbent in wastewater treatment plant which is not only an environment-friendly approach but also may reduce cost of tertiary treatment at sewage treatment plant often required to remove emerging contaminants.